2013
DOI: 10.4103/0300-1652.108897
|View full text |Cite
|
Sign up to set email alerts
|

Childhood acquired heart diseases in Jos, north central Nigeria

Abstract: Background:The patterns of childhood acquired heart diseases (AHD) vary in different parts of the world and may evolve over time. We aimed to compare the pattern of childhood AHD in our institution to the historical and contemporary patterns in other parts of the country, and to highlight possible regional differences and changes in trend.Materials and Methods:Pediatric echocardiography records spanning a period of 10 years were reviewed. Echocardiography records of children with echocardiographic or irrefutab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
(58 reference statements)
3
21
0
Order By: Relevance
“…This is consistent with the result from Nigeria where the mean age of children with RHD was recorded to be 10.8 ± 3.2 years. 10 Females were slightly more affected in this study with male to female ratio of 0.9:1 which is similar to studies done in different parts of the world. 11 Further we have observed that girls with RHD are slightly younger than boys, similar to observation made by Shrestha et al where RHD was commoner in girls and affecting them at a younger age.…”
Section: Discussionsupporting
confidence: 77%
“…This is consistent with the result from Nigeria where the mean age of children with RHD was recorded to be 10.8 ± 3.2 years. 10 Females were slightly more affected in this study with male to female ratio of 0.9:1 which is similar to studies done in different parts of the world. 11 Further we have observed that girls with RHD are slightly younger than boys, similar to observation made by Shrestha et al where RHD was commoner in girls and affecting them at a younger age.…”
Section: Discussionsupporting
confidence: 77%
“…This agrees with findings from other similar studies which reported that indexing echocardiographic parameters to BSA produces more reliable data [2,6]. The study by [10] described only the profile of cardiomyopathy in Nigeria among children in Jos Northern part of Nigeria. Another study by [9] in western Nigeria also described only the profile of cardiomyopathy in Nigeria among children in the region.…”
Section: Baseline Normal Echocardiographic Values Of the Left Ventriclesupporting
confidence: 90%
“…[7,24] Female preponderance was also observed among the study patients with RHD, which is consistent with a previous study in Jos, North-Central Nigeria. [2] In contrast, DCM was most prevalent among under-five children whereas children with EMF and PE were all above the age of 10 years. A recent study by Bode-Thomas et al [2] has similarly observed that DCM was commoner among children below the age of 5-year and RHD was most prevalent in older children above 5-year.…”
Section: Discussionmentioning
confidence: 93%
“…Though known to have global distribution, their relative burden and pattern of distribution vary between regions across the world and even within a particular geographical area. [1,2] In developed countries, for example, Kawasaki disease (KD) is recognized as the leading cause of AHD in children; whereas preventable conditions such as rheumatic heart diseases (RHDs), endomyocardial fibrosis (EMF), tuberculous pericarditis and other infections-related AHDs are quite prevalent in many developing countries. [3] This is due to the endemic poverty, widespread malnutrition, poor living conditions, low immunization coverage for tuberculosis and worsening HIV pandemic in these countries.…”
Section: Introductionmentioning
confidence: 99%